(untitled) (Journal of Intellectual Property Rights (JIPR), 2025)
The Information and Communication Technology (ICT) industry stands as the vanguard of the modern digital age, driving innovation, connectivity, and economic growth on a global scale. At its core, this dynamic sector thrives on the seamless integration of standardized technologies that enable interoperability and foster technological progress. Standard Essential Patents (SEPs) and the Fair, Reasonable, and Non-Discriminatory (FRAND) licensing commitments associated with ICT play a pivotal role in the complex intricacies of global standardization.SEPs are patents that encompass essential technologies to comply with industry standards and norms. SEPs play a crucial role in shaping the ICT landscape to ensure the effective communication and interaction of diverse devices, systems and networks. Interplay of SEPs, FRAND Terms and ICT have profound implications giving rise to a complex terrain of social, legal, economic and technological challenges, especially in a developing country like India. This research paper is an attempt to shed light on the factors influencing technological advancement, competitive landscape, and accessibility of essential technologies in the ever-evolving domain of ICT. The researchers seek to untangle the multifaceted complex web of SEPS and FRAND Licensing, fostering an enhanced understanding of their influence on the present and future of the ICT Industry. Further, challenges faced by the innovators, technology providers and licensees when navigating through this technological landscape are also discussed. Lastly, this paper aims to provide potential solutions and valuable insights to the policymakers, industry stakeholders and intellectual property holders to grapple with the intricate balance between Innovation and accessibility within the context of India’s rapidly evolving mobile technology landscape.